Characterization of Sulfur Compounds in MTBE. (21st June 2015) - Wu, Mingqing; Chang, Chunyan; Li, Tao; Zhou, Jian; Zhao, Liping
Abstract : A study is carried out on chemical constitution of sulfur compounds in MTBE and their formation mechanisms. These sulfur compounds are classified into three types: common sulfur compounds, newly formed sulfur compounds, and high boiling sulfur compounds. Common sulfur compounds which include mercaptans, low molecule sulfides and disulfides, are directly from C4, one of the stocks for production of MTBE. The newly formed sulfur compounds, with one sulfur atom and five or more total carbon atoms in one molecule, are mainly tert -butyl methyl sulfide and tert -butyl ethyl sulfide, thioetherification products of thiols with butenes. Many high boiling sulfur compounds, including polysulfides such as dimethyl trisulfide, multisulfur heterocyclic compounds such as 3, 5-dimethyl-1, 2, 4-trithiolane, and oxygen-containing sulfur compounds such as 2-methoxy-3-methylthio-butane, are also found newly formed in the processes of LPG refining and succedent etherification reaction for producing MTBE. Polysulfides are additional products of elemental sulfur to disulfides, and other high boiling sulfur compounds may be formed by thiols reacting with dienes.